Stacked body of inorganic substrate and transparent heat-resistant polymer film
Patent Information
- Application Number
- CN202280048766.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-07-16
- Filing Date
- 2022-07-07
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-07-07
AI Technical Summary
若该振动的振幅变大,则会出现如下问题:机械臂之间可能无法顺利交接层叠体;在装置内由升降销(lift pin)抬升层叠体时,层叠体的振动变大位置可能会发生偏移等等
[0013] The laminate of this invention exhibits low vibration amplitude during operation, which can suppress positional shifts during processes such as glass handover using machinery and the use of lifting pins. This invention is particularly effective in large-size inorganic substrate systems used for increasing glass vibration amplitude.
Smart Images

Figure BDA0004656070690000251 
Figure HDA0004656070700000011
Abstract
Description
Technical Field
[0001] This invention relates to a laminate in which a heat-resistant polymer film, such as a polyimide resin, is formed on an inorganic substrate. The laminate of this invention is useful, for example, in manufacturing flexible devices and flexible circuit boards in which electronic components are formed on the surface of a flexible substrate. Background Technology
[0002] Research is underway on the use of heat-resistant polymer films such as polyimide (hereinafter referred to simply as "polymer films") as substrate materials for the manufacture of flexible electronic devices. Since such polymer films as polyimide are manufactured into long strips or rolls, roll-to-roll production lines are generally considered ideal for the manufacture of flexible devices. On the other hand, most electronic devices such as display devices, sensor arrays, touch screens, and printed circuit boards in the past used rigid substrates such as glass substrates, semiconductor wafers, or glass fiber reinforced epoxy boards, and the construction of their manufacturing equipment was based on the premise of using such rigid substrates.
[0003] Against this backdrop, a known method for manufacturing flexible electronic devices using existing manufacturing equipment is as follows: A rigid inorganic substrate, such as a glass substrate, is used as a temporary support; a polymer film is temporarily bonded to the temporary support; electronic devices are processed on the polymer film; and the polymer film with the electronic devices is peeled off from the temporary support. Flexible electronic devices are manufactured through this process. (Patent Document 1)
[0004] Furthermore, as a method for manufacturing flexible electronic devices using existing manufacturing equipment, the following method is known: using a rigid substrate such as a glass substrate as a temporary support, coating the temporary support with a polymer solution or a polymer precursor solution, drying to form a precursor film, then converting the precursor into a polymer film through a chemical reaction to obtain a laminate of the temporary support and the polymer film, then forming an electronic device on the polymer film using the same method, and finally peeling it off to manufacture a flexible electronic device. (Patent Document 2)
[0005] However, in the process of forming the desired functional element on a laminate composed of a polymer film and an inorganic support, the laminate is often exposed to high temperatures. For example, when forming functional elements such as polycrystalline silicon or oxide semiconductors, processes in the temperature range of approximately 200°C to 600°C are required. Furthermore, in the fabrication of hydrogenated amorphous silicon films, temperatures of approximately 200°C to 300°C are sometimes applied to the film, and sometimes the amorphous silicon is further heated to dehydrogenate it into low-temperature polycrystalline silicon, requiring heating to approximately 450°C to 600°C. Therefore, although the polymer film constituting the laminate is required to have heat resistance, the practical problem is that there are limited polymer films that can withstand the aforementioned high-temperature ranges, and polyimide is often chosen in most cases.
[0006] In other words, regardless of the method, a laminate is required where a rigid temporary support and a polymer film layer, which is ultimately peeled off to become a flexible electronic device substrate, overlap. Since this laminate can be treated as a rigid sheet material, it can be operated in the same way as glass substrates using the same equipment conventionally used to manufacture liquid crystal displays, plasma displays, or organic EL displays that use glass substrates. [Existing Technical Documents] [Patent Documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 5152104 [Patent Document 2] Japanese Patent Application Publication No. 5699606 Summary of the Invention [The problem the invention aims to solve]
[0008] Laminates of heat-resistant polymer films and inorganic substrates can be handled in display manufacturing processes using robotic arms or vacuum lifts for glass transport. Generally, the glass used in displays is less than 700 μm thick, and this movement during handling by robotic arms causes vibrations along the thickness direction at the glass edges. This vibration amplitude is particularly pronounced when the laminate is large, specifically exceeding 400 mm on one side. Increased amplitude can lead to problems such as: difficulty in smoothly transferring the laminate between robotic arms; and potential displacement of the laminate due to increased vibration when lifted by lift pins within the device.
[0009] Therefore, the present invention solves the above-mentioned problems discovered by the inventors, and its object is to provide a laminate of a heat-resistant polymer film and an inorganic substrate that can suppress the amplitude during operation. [Technical means to solve the problem]
[0010] The inventors conducted in-depth research to solve the above-mentioned problems and found that by controlling the product of the elastic modulus and thickness of the laminate of the heat-resistant polymer film and the inorganic substrate within a certain range, the vibration of the laminate can be suppressed, and thus the present invention was completed.
[0011] That is, the present invention comprises the following components.
[0012] [1] A laminate, characterized in that it is a laminate of a heat-resistant polymer film and an inorganic substrate that is substantially adhesive-free, wherein the heat-resistant polymer film is a transparent heat-resistant polymer film, and the tensile modulus E1 (GPa) and thickness T1 (μm) of the laminate satisfy equation (1): 25000≤E1×T1 (1), Furthermore, the storage modulus E2 (GPa) of the laminate at 280℃ and its thickness T1 (μm) satisfy equation (2): E2×T1≤52000 (2). [2] According to the laminate described in [1], the tensile modulus of the heat-resistant polymer film is above 3.5 GPa and below 9 GPa. [3] The laminate according to any one of [1] to [2] is characterized in that the heat-resistant polymer film has a storage modulus of 9 GPa or less at 280°C. [4] The laminate according to any one of [1] to [3] is characterized in that the heat shrinkage rate of the heat-resistant polymer film when heated from 23°C to 250°C is less than ±0.9%. [5] The laminate according to any one of [1] to [4] is characterized in that the outer diameter of the inorganic substrate is 400 mm or more. [6] The laminate according to any one of [1] to [5] is characterized in that the warpage of the laminate after heating at 280°C for 1 hour is less than 500 μm. [7] The laminate according to any one of [1] to [6] is characterized in that the heat-resistant polymer film comprises at least one selected from polyimide, polyamide and polyamide-imide. [The effects of the invention]
[0013] The laminate of this invention exhibits low vibration amplitude during operation, which can suppress positional shifts during processes such as glass handover using machinery and the use of lifting pins. This invention is particularly effective in large-size inorganic substrate systems used for increasing glass vibration amplitude. Attached Figure Description
[0014] Figure 1 is a schematic diagram of an example of a silane coupling agent coating apparatus according to an embodiment of the present invention. Explanation of reference numerals in the attached figures 1: Flow meter 2: Gas Inlet 3: Reagent container (silane coupling agent container) 4: Hot water tank (hot water bath) 5: Heater 6: Processing Room 7: Substrate 8: Exhaust port Detailed Implementation
[0015] The embodiments of the present invention will be described below.
[0016] <Heat-resistant polymer film> The heat-resistant polymer film of the present invention is a transparent heat-resistant polymer film (hereinafter simply referred to as a polymer film). Examples of the above-mentioned heat-resistant polymer film include polyimide resins such as polyamide-imide, polyether-imide, and fluorinated polyimide (e.g., aromatic polyimide resins, alicyclic polyimide resins); polyamide; aromatic polyamide; polyamide-imide films, etc. However, since the aforementioned polymer films are intended for use in processes involving heat treatment at temperatures above 300°C, the number of practically applicable polymer films among the examples is very limited. Among the aforementioned polymer films, films made of so-called super engineering plastics are preferred; more specifically, aromatic polyimide films, aromatic amide films, and aromatic amide-imide films are examples. The heat-resistant polymer film of the present invention preferably contains at least one selected from polyimide, polyamide, and polyamide-imide.
[0017] The following is a detailed description of a polyimide-based resin film (sometimes also called a polyimide film or a transparent polyimide film), one example of the aforementioned polymer film. Typically, a polyimide-based resin film is obtained by coating a polyamic acid (polyimide precursor) solution, obtained by reacting a diamine with a tetracarboxylic acid in a solvent, onto a support for making a polyimide film, drying it to form a green film (hereinafter also referred to as a "polyamic acid film"), and further subjecting the green film to a high-temperature heat treatment on the polyimide film support or in a state peeled from the support to undergo a ring-closure dehydration reaction.
[0018] The coating of polyamic acid (polyimide precursor) solutions can be carried out using existing known solution coating methods, such as spin coating, doctor blade coating, applicator, comma coating machine, screen printing, slot coating, reverse coating, dip coating, curtain coating, and slot die coating.
[0019] The transparency of the transparent polyimide is preferably 75% or higher in total light transmittance. More preferably, it is 80% or higher, even more preferably 85% or higher, and still more preferably 87% or higher, particularly preferably 88% or higher. There is no particular upper limit to the total light transmittance of the above-mentioned transparent polyimide, but for use in flexible electronic devices, it is preferably 98% or lower, more preferably 97% or lower. The colorless transparent polyimide in this invention is preferably a polyimide with a total light transmittance of 75% or higher. The method for measuring the total light transmittance of the above-mentioned polymer film is the method described in the examples.
[0020] To obtain colorless and transparent polyimides, aromatic tetracarboxylic acids can be listed as follows: 4,4'-(2,2-hexafluoroisopropylidene) phthalic acid, 4,4'-oxobisphthalic acid, bis(1,3-dioxo-1,3-dihydro-2-benzofuran-5-acid) 1,4-phenylene ester, bis(1,3-dioxo-1,3-dihydro-2-benzofuran-5-yl) phenyl-1,4-diester, 4,4'-[4,4'-(3-oxo-1,3-dihydro-2-benzofuran-1,1-diyl)bis(phenyl-1,4-diyloxy)] diphenyl-1,2-dicarboxylic acid, 3,3',4,4'-benzophenone tetracarboxylic acid, 4,4'-[(3-oxo-1,3-dihydro-2-benzofuran-1,1-diyl)bis(phenyl-1,4-diyloxy)] diphenyl-1,2-dicarboxylic acid, 3,3',4,4'-benzophenone tetracarboxylic acid, 4,4'-[(3-oxo-1,3-dihydro-2-benzofuran-1,4 ... [1-diyl)bis(toluene-2,5-diyloxy)]diphenyl-1,2-dicarboxylic acid, 4,4'-[(3-oxo-1,3-dihydro-2-benzofuran-1,1-diyl)bis(1,4-xylene-2,5-diyloxy)]diphenyl-1,2-dicarboxylic acid, 4,4'-[4,4'-(3-oxo-1,3-dihydro-2-benzofuran-1,1-diyl)bis(4-isopropyl-toluene-2,5-diyloxy)]diphenyl-1,2-dicarboxylic acid, 4,4'-[4,4'-(3-oxo-1,3-dihydro-2-benzofuran-1,1-diyl)bis(naphthalene-1,4-diyloxy)]diphenyl-1,2-dicarboxylic acid, 4,4'-[4,4'-(3H-2, 1-Benzoxathia-1,1-dioxane-3,3-diyl)bis(benzene-1,4-diyloxy)]diphenyl-1,2-dicarboxylic acid, 4,4'-benzophenone tetracarboxylic acid, 4,4'-[(3H-2,1-benzooxathia-1,1-dioxane-3,3-diyl)bis(toluene-2,5-diyloxy)]diphenyl-1,2-dicarboxylic acid, 4,4'-[(3H-2,1-benzooxathia-1,1-dioxane-3,3-diyl)bis(1,4-xylene-2,5-diyloxy)]diphenyl-1,2-dicarboxylic acid, 4,4'-[4,4'-(3H-2,1-benzooxathia-1,1-dioxane-3,3-diyl)bis(4-isopropyl-toluene-2,5-diyloxy)]diphenyl-1,2-dicarboxylic acid Benzene-1,2-diacid, 4,4'-[4,4'-(3H-2,1-benzoxyl-1,1-dioxane-3,3-diyl)bis(naphthalene-1,4-diyloxy)]diphenyl-1,2-diacid, 3,3',4,4'-benzophenone tetracid, 3,3',4,4'-benzophenone tetracid, 3,3',4,4'-diphenylsulfone tetracid Tetracarboxylic acids and their anhydrides, including 3,3',4,4'-biphenyltetracarboxylic acid, 2,3,3',4'-biphenyltetracarboxylic acid, pyromellitic acid, 4,4'-[spiro(xanthan-9,9'-fluorene)-2,6-dimethylbis(oxycarbonyl)]diphthalic acid, and 4,4'-[spiro(xanthan-9,9'-fluorene)-3,6-dimethylbis(oxycarbonyl)]diphthalic acid.Preferably, the dianhydride has two anhydride structures, particularly preferably 4,4'-(2,2-hexafluoroisopropylidene)bisphthalic dianhydride and 4,4'-oxobisphthalic dianhydride. Furthermore, aromatic tetracarboxylic acids can be used alone or in combination of two or more. When heat resistance is important, the copolymerization amount of the aromatic tetracarboxylic acid is, for example, preferably 50% by mass or more of all tetracarboxylic acids, more preferably 60% by mass or more, further preferably 70% by mass or more, even more preferably 80% by mass or more, particularly preferably 90% by mass or more, and may also be 100% by mass.
[0021] Alicyclic tetracarboxylic acids include 1,2,3,4-cyclobutanetetracarboxylic acid, 1,2,3,4-cyclopentanetetracarboxylic acid, 1,2,3,4-cyclohexanetetracarboxylic acid, 1,2,4,5-cyclohexanetetracarboxylic acid, 3,3',4,4'-dicyclohexyltetracarboxylic acid, bicyclo[2,2,1]heptane-2,3,5,6-tetracarboxylic acid, and bicyclo[2,2,2]octane-2,3,5,6-tetracarboxylic acid. 6-Tetracarboxylic acid, bicyclo[2,2,2]oct-7-ene-2,3,5,6-tetracarboxylic acid, tetrahydroanthracene-2,3,6,7-tetracarboxylic acid, tetradecahydro-1,4:5,8:9,10-trimethylbridged anthracene-2,3,6,7-tetracarboxylic acid, decahydronaphthalene-2,3,6,7-tetracarboxylic acid, decahydro-1,4:5,8-dimethylbridged naphthalene-2,3,6,7-tetracarboxylic acid, decahydro-1 ,4-Ethanol-5,8-methylnaphthalene-2,3,6,7-tetracarboxylic acid, norbornane-2-spiro-α-cyclopentanone-α'-spiro-2”-norbornane-5,5”,6,6”-tetracarboxylic acid (also known as "norbornane-2-spiro-2'-cyclopentanone-5'-spiro-2”-norbornane-5,5”,6,6”-tetracarboxylic acid"), methylnorbornane-2-spiro-α-cyclopentanone-α'-spiro-2”-(methylnorbornane)-5,5',6,6”-tetracarboxylic acid, norbornane-2-spiro-α-cyclohexanone-α'-spiro-2”-norbornane-5,5”,6,6”-tetracarboxylic acid (also known as "norbornane-2-spiro-2'-cyclohexanone-6'-spiro-2”-norbornane-5,5”,6,6”-tetracarboxylic acid"), methylnorbornane-2-spiro-α-cyclohexanone-α'-spiro-2”-norbornane-5,5”,6,6”-tetracarboxylic acid, methylnorbornane-2-spiro-2'-cyclohexanone-6'-spiro-2”-norbornane-5,5”,6,6”-tetracarboxylic acid), methylnorbornane-2-spiro-α ..., methylnorbornane-2-spiro-α-cyclohexanone-6'-spir Norbornane-2-spiro-α-cyclohexanone-α'-spiro-2”-(methylnorbornane)-5,5',6,6”-tetracarboxylic acid, norbornane-2-spiro-α-cyclopropanone-α'-spiro-2”-norbornane-5,5”,6,6”-tetracarboxylic acid, norbornane-2-spiro-α-cyclobutanone-α'-spiro-2”-norbornane-5,5”,6,6” -Tetracarboxylic acid, norbornane-2-spiro-α-cycloheptanone-α'-spiro-2”-norbornane-5,5”,6,6”-Tetracarboxylic acid, norbornane-2-spiro-α-cyclooctanone-α'-spiro-2”-norbornane-5,5”,6,6”-Tetracarboxylic acid, norbornane-2-spiro-α-cyclononanone-α'-spiro-2”-norbornane-5,5”,6,6”-Tetracarboxylic acid, norbornane-2-spiro-α-cyclononanone-α'-spiro-2”-norbornane-5,5”,6,6”-Tetracarboxylic acid Borneol, norbornane-2-spiro-α-cyclononanone-α'-spiro-2”-norbornane-5,5”,6,6”-tetracarboxylic acid, norbornane-2-spiro-α-cyclodecanone-α'-spiro-2”-norbornane-5,5”,6,6”-tetracarboxylic acid, norbornane-2-spiro-α-cycloundecanone-α'-spiro-2”-norbornane-5,5”,6,6”-tetracarboxylic acid, norbornane-2-spiro-α-cycloundecanone-α'-spiro-2”-norbornane-5,5”,6,6”-tetracarboxylic acid Acid, norbornane-2-spiro-α-cyclododecanoone-α'-spiro-2”-norbornane-5,5”,6,6”-tetracarboxylic acid, norbornane-2-spiro-α-cyclotridecanone-α'-spiro-2”-norbornane-5,5”,6,6”-tetracarboxylic acid, norbornane-2-spiro-α-cyclotetradecanoone-α'-spiro-2”-norbornane-5,5”,6,6”-tetracarboxylic acid, norbornane-2-spiro-α-cyclotetradecanoone-α'-spiro-2”-norbornane-5,5”,6,Tetracarboxylic acids and their anhydrides, including 6”-tetracarboxylic acid, norbornane-2-spiro-α-cyclopentadecanone-α'-spiro-2”-norbornane-5,5”,6,6”-tetracarboxylic acid, norbornane-2-spiro-α-(methylcyclopentanone)-α'-spiro-2”-norbornane-5,5”,6,6”-tetracarboxylic acid, norbornane-2-spiro-α-(methylcyclohexanone)-α'-spiro-2”-norbornane-5,5”,6,6”-tetracarboxylic acid. Among them, dianhydrides having two anhydride structures are preferred, particularly 1,2,3,4-cyclobutanetetracarboxylic dianhydrides, 1,2,3,4-cyclohexanetetracarboxylic dianhydrides, and 1,2,4,5-cyclohexanetetracarboxylic dianhydrides, more preferably 1,2,3,4-cyclobutanetetracarboxylic dianhydrides and 1,2,4,5-cyclohexanetetracarboxylic dianhydrides, and even more preferably 1,2,3,4-cyclobutanetetracarboxylic dianhydrides. Furthermore, these can be used alone or in combination of two or more. When heat resistance is important, the copolymerization amount of the alicyclic tetracarboxylic acid is, for example, preferably 50% by mass or more of all tetracarboxylic acids, more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, particularly preferably 90% by mass or more, and even 100% by mass is acceptable.
[0022] Tricarboxylic acids include aromatic tricarboxylic acids such as trimellitic acid, 1,2,5-naphthalenetrilic acid, diphenyl ether-3,3',4'-tricarboxylic acid, and diphenyl sulfone-3,3',4'-tricarboxylic acid, or hydrogenation products of the above aromatic tricarboxylic acids such as hexahydrotriphenylamine, alkylene glycol bis(triphenylamine) esters such as ethylene glycol bis(triphenylamine) ester, glycerol bis(triphenylamine) ester, 1,4-butanediol bis(triphenylamine) ester, and polyethylene glycol bis(triphenylamine) ester, and their monoanhydrides and ester compounds. Among these, monoanhydrides having one anhydride structure are preferred, especially trimellitic anhydride and hexahydrotriphenylamine anhydride. Furthermore, these can be used alone or in combination.
[0023] Dicarboxylic acids include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, and 4,4'-oxydibenzenecarboxylic acid, or hydrogenation products of the above aromatic dicarboxylic acids such as 1,6-cyclohexanedicarboxylic acid, oxalic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, octanoic acid, azelaic acid, sebacic acid, undecanoic acid, dodecanoic acid, 2-methylsuccinic acid, and their acyl chlorides or ester compounds. Aromatic dicarboxylic acids and their hydrogenation products are preferred, especially terephthalic acid, 1,6-cyclohexanedicarboxylic acid, and 4,4'-diphenylzenecarboxylic acid. Furthermore, these dicarboxylic acids can be used alone or in combination.
[0024] There are no particular limitations on the diamines or isocyanates used to obtain colorless and transparent polyimides. Aromatic diamines, aliphatic diamines, alicyclic diamines, aromatic diisocyanates, aliphatic diisocyanates, and alicyclic diisocyanates commonly used in the synthesis of polyimides, polyamide-imides, and polyamides can be used. From the viewpoint of heat resistance, aromatic diamines are preferred, and from the viewpoint of transparency, alicyclic diamines are preferred. Furthermore, when using aromatic diamines containing a benzoxazole structure, high heat resistance, high elastic modulus, low thermal shrinkage, and low linear expansion coefficient may also be observed. Diamines and diisocyanates can be used alone or in combination.
[0025] Aromatic diamines include, for example, 2,2'-dimethyl-4,4'-diaminobiphenyl, 1,4-bis[2-(4-aminophenyl)-2-propyl]benzene, 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene, 2,2'-ditrifluoromethyl-4,4'-diaminobiphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, bis[4-(3-aminophenoxy)phenyl]ketone, bis[4-(3-aminophenoxy)phenyl]sulfide, bis[4-(3-aminophenoxy)phenyl]sulfone, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, and 2,2-bis[4-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane. Alkane, m-phenylenediamine, o-phenylenediamine, p-phenylenediamine, m-aminobenzylamine, p-aminobenzylamine, 4-amino-N-(4-aminophenyl)benzamide, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 2,2'-trifluoromethyl-4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfoxide, 3,4'-diaminodiphenyl sulfoxide, 4,4'-diaminodiphenyl sulfoxide, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminobenzophenone, 3,4'-diaminodiphenyl ketone Benzophenone, 4,4'-diaminobenzophenone, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, bis[4-(4-aminophenoxy)phenyl]methane, 1,1-bis[4-(4-aminophenoxy)phenyl]ethane, 1,2-bis[4-(4-aminophenoxy)phenyl]ethane, 1,1-bis[4-(4-aminophenoxy)phenyl]propane, 1,2-bis[4-(4-aminophenoxy)phenyl]propane, 1,3-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 1,1-bis[4-(4-aminophenoxy)phenyl]butane, 1,3-bis[4-(4-aminophenoxy)phenyl]butane, [4-(4-aminophenoxy)phenyl]butane, 1,4-bis[4-(4-aminophenoxy)phenyl]butane, 2,2-bis[4-(4-aminophenoxy)phenyl]butane, 2,3-bis[4-(4-aminophenoxy)phenyl]butane, 2-[4-(4-aminophenoxy)phenyl]-2-[4-(4-aminophenoxy)-3-methylphenyl]propane, 2,2-bis[4-(4-aminophenoxy)-3-methylphenyl]propane, 2-[4-(4-aminophenoxy)phenyl]-2-[4-(4-aminophenoxy)-3,5-dimethylphenyl]propane, 2,2-bis[4-(4-aminophenoxy)-3,5-dimethylphenyl]propane, 2,2-bis[4-(4-aminophenoxy)-3,5-dimethylphenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-Hexafluoropropane, 1,4-bis(3-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis[4-(4-aminophenoxy)phenyl]ketone, bis[4-(4-aminophenoxy)phenyl]sulfide, bis[4-(4-aminophenoxy)phenyl]sulfoxide, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(4-aminophenoxy)phenyl]ether, 1,3-bis[4-(4-aminophenoxy)benzoyl]benzene, 1,3-bis[4-(3-aminophenoxy)benzoyl]benzene, 1,4-bis[4-(3-aminophenoxy)benzoyl]benzene [-aminophenoxy)benzoyl]benzene, 4,4'-bis[(3-aminophenoxy)benzoyl]benzene, 1,1-bis[4-(3-aminophenoxy)phenyl]propane, 1,3-bis[4-(3-aminophenoxy)phenyl]propane, 3,4'-diaminodiphenyl sulfide, 2,2-bis[3-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, bis[4-(3-aminophenoxy)phenyl]methane, 1,1-bis[4-(3-aminophenoxy)phenyl]ethane, 1,2-bis[4-(3-aminophenoxy)phenyl]ethane, bis[4-(3-aminophenoxy)phenyl]sulfoxide, 4,4'-bis[3-(4-aminophenoxy)benzoyl]diphenyl ether, 4, 4'-bis[3-(3-aminophenoxy)benzoyl]diphenyl ether, 4,4'-bis[4-(4-amino-α,α-dimethylbenzyl)phenoxy]benzophenone, 4,4'-bis[4-(4-amino-α,α-dimethylbenzyl)phenoxy]diphenyl sulfone, bis[4-{4-(4-aminophenoxy)phenoxy}phenyl]sulfone, 1,4-bis[4-(4-aminophenoxy)phenoxy-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-aminophenoxy)phenoxy-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-amino-6-trifluoromethylphenoxy)-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-amino-6-trifluoromethylphenoxy)-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-amino-6-fluorophenoxy)-α,α-diphenyl]benzene, [Methylbenzyl]benzene, 1,3-bis[4-(4-amino-6-methylphenoxy)-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-amino-6-cyanophenoxy)-α,α-dimethylbenzyl]benzene, 3,3'-diamino-4,4'-diphenoxybenzophenone, 4,4'-diamino-5,5'-diphenoxybenzophenone, 3,4'-diamino-4,5'-diphenoxybenzophenone, 3,3'-diamino-4-phenoxybenzophenone, 4,4'-diamino-5-phenoxybenzophenone, 3,4'-diamino-4-phenoxybenzophenone, 3,4'-diamino-5'-phenoxybenzophenone, 3,3'-diamino-4,4'-dibiphenoxybenzophenone, 4,4'-Diamino-5,5'-Diphenyloxybenzophenone, 3,4'-Diamino-4,5'-Diphenyloxybenzophenone, 3,3'-Diamino-4-Biphenyloxybenzophenone, 4,4'-Diamino-5-Biphenyloxybenzophenone, 3,4'-Diamino-4-Biphenyloxybenzophenone, 3,4'-Diamino-5'-Biphenyloxybenzophenone, 1,3-bis(3-amino-4-phenoxybenzoyl)benzene, 1,4-bis(3-amino-4-phenoxybenzoyl)benzene, 1,3-bis(4-amino-5-phenoxybenzoyl)benzene, 1,4-bis(4-amino-5-phenoxybenzoyl)benzene, 1,3-bis(3-amino-4-biphenyloxybenzoyl)benzene, 1,4 -bis(3-amino-4-biphenoxybenzoyl)benzene, 1,3-bis(4-amino-5-biphenoxybenzoyl)benzene, 1,4-bis(4-amino-5-biphenoxybenzoyl)benzene, 2,6-bis[4-(4-amino-α,α-dimethylbenzyl)phenoxy]benzonitrile, 4,4'-[9H-fluorene-9,9-diyl]bisaniline ( Other names include "9,9-bis(4-aminophenyl)fluorene", spiro(xanthon-9,9'-fluorene)-2,6-diylbis(oxycarbonyl)]bisaniline, 4,4'-[spiro(xanthon-9,9'-fluorene)-2,6-diylbis(oxycarbonyl)]bisaniline, and 4,4'-[spiro(xanthon-9,9'-fluorene)-3,6-diylbis(oxycarbonyl)]bisaniline. Furthermore, some or all of the hydrogen atoms on the aromatic ring of the above-mentioned aromatic diamines can be replaced by halogen atoms, alkyl or alkoxy groups having 1 to 3 carbon atoms, or cyano groups; and furthermore, some or all of the hydrogen atoms in the alkyl or alkoxy groups having 1 to 3 carbon atoms can also be replaced by halogen atoms. Furthermore, the aromatic diamines containing the benzoxazole structure mentioned above are not particularly limited, and examples include 5-amino-2-(p-aminophenyl)benzoxazole, 6-amino-2-(p-aminophenyl)benzoxazole, 5-amino-2-(m-aminophenyl)benzoxazole, 6-amino-2-(m-aminophenyl)benzoxazole, 2,2'-p-phenylenebis(5-aminobenzoxazole), 2,2'-p-phenylenebis(6-aminobenzoxazole), 1-(5-aminobenzoxazole)-4-(6-aminobenzoxazole)benzene, and 2,6-(4,4'-diaminodiphenyl)benzo[1,2] Bisoxazole, 2,6-(4,4'-diaminodiphenyl)benzo[1,2-d:4,5-d']bisoxazole, 2,6-(3,4'-diaminodiphenyl)benzo[1,2-d:5,4-d']bisoxazole, 2,6-(3,4'-diaminodiphenyl)benzo[1,2-d:4,5-d']bisoxazole, 2,6-(3,3'-diaminodiphenyl)benzo[1,2-d:5,4-d']bisoxazole, 2,6-(3,3'-diaminodiphenyl)benzo[1,2-d:4,5-d']bisoxazole, etc., among which 2,2'-Ditrifluoromethyl-4,4'-diaminobiphenyl, 4-amino-N-(4-aminophenyl)benzamide, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminobenzophenone. In addition, aromatic diamines can be used alone or in combination.
[0026] Examples of alicyclic diamines include 1,4-diaminocyclohexane, 1,4-diamino-2-methylcyclohexane, 1,4-diamino-2-ethylcyclohexane, 1,4-diamino-2-n-propylcyclohexane, 1,4-diamino-2-isopropylcyclohexane, 1,4-diamino-2-n-butylcyclohexane, 1,4-diamino-2-isobutylcyclohexane, 1,4-diamino-2-sec-butylcyclohexane, 1,4-diamino-2-tert-butylcyclohexane, and 4,4'-methylenebis(2,6-dimethylcyclohexylamine). Among these, 1,4-diaminocyclohexane and 1,4-diamino-2-methylcyclohexane are particularly preferred, and 1,4-diaminocyclohexane is more preferred. Furthermore, alicyclic diamines can be used alone or in combination.
[0027] Examples of diisocyanates include diphenylmethane-2,4'-diisocyanate, 3,2'- or 3,3'- or 4,2'- or 4,3'- or 5,2'- or 5,3'- or 6,2'- or 6,3'-dimethyldiphenylmethane-2,4'-diisocyanate, 3,2'- or 3,3'- or 4,2'- or 4,3'- or 5,2'- or 5,3'- or 6,2'- or 6,3'-diethyldiphenylmethane-2 4'-Diisocyanate, 3,2'- or 3,3'- or 4,2'- or 4,3'- or 5,2'- or 5,3'- or 6,2'- or 6,3'-dimethoxydiphenylmethane-2,4'-diisocyanate, diphenylmethane-4,4'-diisocyanate, diphenylmethane-3,3'-diisocyanate, diphenylmethane-3,4'-diisocyanate, diphenyl ether-4,4'-diisocyanate, benzophenone-4,4'-diisocyanate -Diisocyanate, diphenyl sulfone-4,4'-diisocyanate, toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, m-phenylenedimethyl isocyanate, terephthalic dimethyl isocyanate, naphthalene-2,6-diisocyanate, 4,4'-(2,2-bis(4-phenoxyphenyl)propane)diisocyanate, 3,3'- or 2,2'-dimethylbiphenyl-4,4'-diisocyanate, 3,3'- or 2,2'-diethyl Aromatic diisocyanates such as biphenyl-4,4'-diisocyanate, 3,3'-dimethoxybiphenyl-4,4'-diisocyanate, and 3,3'-diethoxybiphenyl-4,4'-diisocyanate, as well as hydrogenated diisocyanates of any one of them (e.g., isophorone diisocyanate, 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, etc.). From the perspectives of low hygroscopicity, dimensional stability, price, and polymerizability, diphenylmethane-4,4'-diisocyanate, toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, 3,3'-dimethylbiphenyl-4,4'-diisocyanate or naphthalene-2,6-diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, and 1,4-cyclohexane diisocyanate are preferred. Furthermore, diisocyanates can be used alone or in combination.
[0028] In this embodiment, the polymer film is preferably a polyimide film. Polyimide films exhibit excellent heat resistance. Furthermore, when the polymer film is polyimide, it can be suitably cut using an ultraviolet laser.
[0029] The thickness of the aforementioned polymer film is preferably 3 μm or more, more preferably 7 μm or more, even more preferably 14 μm or more, and even more preferably 20 μm or more. There is no particular upper limit to the thickness of the aforementioned polymer film, but for use as a flexible electronic device, it is preferably 250 μm or less, more preferably 100 μm or less, and even more preferably 50 μm or less.
[0030] The average coefficient of linear expansion (CTE) of the polymer film between 30°C and 250°C is preferably 50 ppm / K or less. More preferably, it is 45 ppm / K or less, even more preferably 40 ppm / K or less, even more preferably 30 ppm / K or less, and particularly preferably 20 ppm / K or less. Furthermore, it is preferably -5 ppm / K or more, more preferably -3 ppm / K or more, and even more preferably 1 ppm / K or more. When the CTE is within the above range, the difference in the coefficient of linear expansion between the polymer film and the ordinary support (inorganic substrate) can be kept small, and even when used in heating processes, peeling of the polymer film from the inorganic substrate or warping of the support can be avoided. Here, CTE represents the factor of reversible expansion and contraction with respect to temperature. In addition, the CTE of the polymer film refers to the average value of the CTE in the coating direction (MD direction) and the CTE in the width direction (TD direction) of the polymer solution or polymer precursor solution. The method for measuring the CTE of the polymer film is the method described in the examples.
[0031] When the aforementioned polymer film is a transparent polyimide film, its yellow index (hereinafter also referred to as "YI") is preferably 10 or less, more preferably 7 or less, even more preferably 5 or less, and even more preferably 3 or less. There is no particular limitation on the lower limit of the yellow index of the aforementioned transparent polyimide; however, for use in flexible electronic devices, it is preferably 0.1 or more, more preferably 0.2 or more, and even more preferably 0.3 or more. The method for determining the YI of the aforementioned polymer film is the method described in the examples.
[0032] When the aforementioned polymer film is a transparent polyimide film, the haze is preferably below 1.0, more preferably below 0.8, even more preferably below 0.5, and even more preferably below 0.3. There is no particular limitation on the lower limit; industrially, a haze above 0.01 is acceptable, and a haze above 0.05 is also permissible. The method for measuring the haze of the aforementioned polymer film is the method described in the examples.
[0033] The thermal shrinkage rate of the above-mentioned polymer film between 23°C and 500°C is preferably ±0.9% or less, more preferably ±0.6% or less, and even more preferably ±0.2% or less. The thermal shrinkage rate represents the factor of irreversible stretching and contraction with respect to temperature. The method for determining the thermal shrinkage rate of the above-mentioned polymer film is the method described in the examples.
[0034] As a method for controlling the thermal shrinkage rate within the aforementioned range, one example is reducing the stress applied to the polymer film in a heated environment during the fabrication of the polymer film. Specifically, when the polymer film is a polyimide film, this can be achieved by relaxing the tension applied in the MD and TD directions of the film during high-temperature film formation.
[0035] The tensile breaking strength of the aforementioned polymer film is preferably 60 MPa or higher, more preferably 80 MPa or higher, and even more preferably 100 MPa or higher. There is no particular upper limit to the tensile breaking strength; in fact, it is approximately less than 1000 MPa. A tensile breaking strength of 60 MPa or higher can prevent the polymer film from breaking during peeling from the inorganic substrate. Furthermore, the tensile breaking strength of the aforementioned polymer film refers to the average of the tensile breaking strength in the mechanical direction (MD direction) and the tensile breaking strength in the width direction (TD direction).
[0036] The tensile elongation at break of the aforementioned polymer film is preferably 1% or more, more preferably 5% or more, and even more preferably 10% or more. When the tensile elongation at break is 1% or more, the processability is excellent. Furthermore, the tensile elongation at break of the aforementioned polymer film refers to the average of the tensile elongation at break in the mechanical direction (MD direction) and the tensile elongation at break in the width direction (TD direction).
[0037] The tensile modulus of the aforementioned polymer film is preferably 3.5 GPa or higher, more preferably 4 GPa or higher. When the tensile modulus is 3.5 GPa or higher, the tensile deformation of the polymer film is less when peeled from the inorganic substrate, resulting in excellent processability. Furthermore, when the tensile modulus of the polymer film is 3.5 GPa or higher, the amplitude of vibration during transport or handling of the laminate with the inorganic substrate can be kept small. The tensile modulus is preferably 9 GPa or lower, more preferably 8.8 GPa or lower, and more preferably 8.5 GPa or lower. When the tensile modulus is 9 GPa or lower, the polymer film can be used as a flexible film. Furthermore, when the tensile modulus of the polymer film is 9 GPa or lower, warping of the laminate after heating can be suppressed. Moreover, when the tensile modulus of the polymer film is 9 GPa or lower, the storage modulus of the film at 280°C is easily controlled to be 9 GPa or lower. The storage modulus of the polymer film at 280°C is preferably 9 GPa or less, more preferably 0.5 GPa or less, and even more preferably 6 GPa or less. Furthermore, it is preferably 0.1 GPa or more, more preferably 0.5 GPa or more, and even more preferably 1 GPa or more. When the tensile modulus of the polymer film is greater than 9 GPa, the force exerted by the polymer film on the inorganic substrate is large due to thermal shrinkage, thus increasing the warpage of the laminate. Furthermore, when the storage modulus at 280°C is greater than 9 GPa, the force exerted by the polymer film on the inorganic substrate is large. At high temperatures, due to thermal shrinkage and expansion caused by CTE, the dimensional changes in the polymer film can deform the laminate, sometimes increasing the warpage of the laminate. In addition, the tensile modulus and storage modulus of the polymer film mentioned above refer to the average of the tensile modulus in the mechanical direction (MD direction) and the tensile modulus in the width direction (TD direction). The method for measuring the tensile modulus and storage modulus of the polymer film is the method described in the examples.
[0038] The thickness deviation of the aforementioned polymer membrane is preferably 20% or less, more preferably 12% or less, even more preferably 7% or less, and particularly preferably 4% or less. When the thickness deviation is greater than 20%, it tends to be difficult to apply to narrow areas. In addition, the membrane thickness deviation can be measured, for example, by using a contact thickness gauge to randomly select about 10 points on the membrane to be measured, and then calculated according to the following formula. Membrane thickness deviation (%) =100×(maximum film thickness-minimum film thickness)÷average film thickness
[0039] The aforementioned polymer film is preferably manufactured as a long strip of polymer film with a width of 300 mm or more and a length of 10 m or more, and is more preferably in the form of a roll of polymer film wound on a core. When the aforementioned polymer film is wound into a roll, it is easy to transport in the form of a polymer film wound into a roll.
[0040] In the aforementioned polymer membrane, to ensure operability and productivity, it is preferable to add or include about 0.03 to 3% by mass of a lubricant (particles) with a particle size of about 10 to 1000 nm to the polymer membrane, thereby imparting minute irregularities to the surface of the polymer membrane to ensure slippage.
[0041] <Inorganic substrate> The aforementioned inorganic substrate can be any plate-shaped material that is composed of inorganic substances. Examples include substrates made primarily of glass plates, ceramic plates, semiconductor wafers, and metals, as well as substrates formed by stacking composites of these glass plates, ceramic plates, semiconductor wafers, and metals, substrates formed by dispersing these composites, and substrates containing fibers of these substances.
[0042] The aforementioned glass substrates include quartz glass, high-silicate glass (96% silicon dioxide), soda-lime glass, lead glass, aluminosilicate glass, borosilicate glass (PYREX (registered trademark)), borosilicate glass (alkali-free), borosilicate glass (micro-plates), aluminosilicate glass, etc. Among these, a linear expansion coefficient of 5 ppm / K or less is preferred. Commercially available glass substrates preferably include Corning (registered trademark) 7059, Corning (registered trademark) 1737, and EAGLE manufactured by Corning Incorporated; Asahi Glass (registered trademark) AN100 manufactured by Asahi Glass Co., Ltd.; Nippon Electric Glass Co., Ltd.; and SCHOTT Co., Ltd. (registered trademark) AF32 manufactured by SCHOTT Co., Ltd.
[0043] The semiconductor wafers mentioned above are not particularly limited, and may include silicon wafers, germanium wafers, silicon-germanium wafers, gallium-arsenic wafers, aluminum-gallium-indium wafers, nitrogen-phosphorus-arsenic-antimony wafers, SiC, InP (indium phosphorus), InGaAs, GaInNAs, LT, LN, ZnO (zinc oxide), CdTe (cadmium tellurium), ZnSe (zinc selenide), etc. Among them, silicon wafers are preferred, and mirror-polished silicon wafers with a size of 8 feet or more are particularly preferred.
[0044] The aforementioned metals include single-element metals such as W, Mo, Pt, Fe, Ni, and Au, or alloys such as Inconel alloys, Monel alloys, Nimonic alloys, carbon copper, Fe-Ni Invar alloys, and super Invar alloys. This also includes multilayer metal plates formed by adding other metal layers or ceramic layers to these metals. In this case, if the overall coefficient of linear expansion (CTE) with the added layers is low, the main metal layer can be Cu, Al, etc. The metal used as the added metal layer is not particularly limited as long as it possesses properties such as strong adhesion to the transparent heat-resistant polymer film, non-diffusion, chemical resistance, and good heat resistance; examples include Cr, Ni, TiN, and Mo-containing Cu.
[0045] The ceramic plates in this invention include substrate ceramics such as Al2O3, mullite, ALN, SiC, crystalline glass, cordierite, spodumene, Pb-BSG+CaZrO3+Al2O3, crystalline glass+Al2O3, crystalline Ca-BSG, BSG+quartz, BSG+Al2O3, Pb-BSG+Al2O3, glass ceramics, and Zerodur material.
[0046] The planar portion of the aforementioned inorganic substrate is preferably sufficiently flat. Specifically, the surface roughness PV value is 50 nm or less, more preferably 20 nm or less, and even more preferably 5 nm or less. If it is rougher than this, the peel strength between the polymer film and the inorganic substrate may sometimes become insufficient.
[0047] The thickness of the aforementioned inorganic substrate is not particularly limited, but from a processability point of view, it is preferably 10 mm or less, more preferably 3 mm or less, and even more preferably 1.3 mm or less. The lower limit of the thickness is not particularly limited, but it is preferably 0.07 mm or more, more preferably 0.15 mm or more, and even more preferably 0.3 mm or more. If it is too thin, it may be easily damaged and difficult to handle. If it is too thick, it may become heavy and difficult to handle.
[0048] The tensile modulus of the aforementioned inorganic substrate is preferably 50 GPa or higher, more preferably 60 GPa or higher, and even more preferably 65 GPa or higher. Furthermore, the upper limit of the tensile modulus is 80 GPa, and even more preferably 78 GPa or lower. When the tensile modulus of the inorganic substrate is within the above range, its operability is excellent.
[0049] <Layered Body> The laminate of the present invention is a laminate of a heat-resistant polymer film and an inorganic substrate that substantially does not use an adhesive. When the transparent heat-resistant polymer film has a laminated structure with two or more layers, it is preferable to have a transparent polymer film in contact with the inorganic substrate and a transparent heat-resistant polymer film layer that is adjacent to the polymer film layer without contacting the inorganic substrate.
[0050] The shape of the laminate is not particularly limited; it can be square or rectangular. A rectangle is preferred, with the longest side length preferably 300 mm or more, more preferably 500 mm or more, and even more preferably 1000 mm or more. There is no particular upper limit; industrially, a length of 20,000 mm or less is acceptable, and 10,000 mm or less is also acceptable.
[0051] In this invention, when the inorganic substrate is rectangular, it preferably has a circumscribed circle diameter of 400 mm or more. By using an inorganic substrate of this size, the improved operability of the laminate can be fully achieved in this invention. More preferably, it is 450 mm or more, and even more preferably 500 mm or more. Furthermore, there is no particular upper limit; industrially, 1000 mm or less is acceptable, and 800 mm or more is also acceptable.
[0052] In this invention, the tensile modulus E1 and thickness T1 of the laminate of transparent heat-resistant polymer film and inorganic substrate satisfy equation (1). 25000≤E1×T1 (1) E1×T1 is preferably 26,000 or more, more preferably 28,000 or more, even more preferably 30,000 or more, and particularly preferably 35,000 or more. There is no particular upper limit, but preferably 60,000 or less, more preferably 50,000 or less, and even more preferably 45,000 or less. When E1×T1 is within the above range, the amplitude of the inorganic substrate during laminate processing can be reduced. Here, E1 is in GPa, and T1 is in μm.
[0053] The tensile modulus E1 of the laminate is preferably 40 GPa or more, more preferably 50 GPa or more, even more preferably 60 GPa or more, preferably 120 GPa or less, more preferably 100 GPa or less, and even more preferably 80 GPa or less. Furthermore, the thickness T1 of the laminate is preferably 100 μm or more, more preferably 300 μm or more, even more preferably 500 μm or more, preferably 1000 μm or less, more preferably 800 μm or less, and even more preferably 600 μm or less. Within the above ranges, the above formula (1) is easily satisfied. Furthermore, the method for measuring the tensile modulus E1 and thickness T1 of the laminate is the method described in the examples.
[0054] In this invention, the energy storage modulus E2 and thickness T1 of the laminate of transparent heat-resistant polymer film and inorganic substrate at 280°C satisfy equation (2). E2×T1≤52000 (2) E2×T1 is preferably 50,000 or less, more preferably 45,000 or less, even more preferably 42,000 or less, and particularly preferably 40,000 or less. The lower limit is not particularly limited, but preferably 10,000 or more, more preferably 20,000 or more, and even more preferably 25,000 or more. When E2×T1 is within the above range, warping of the laminate during high-temperature heating can be suppressed. Here, E2 is in GPa, and T1 is in μm.
[0055] The storage modulus of the laminate at 280°C is preferably 30 GPa or more, more preferably 50 GPa or more, even more preferably 70 GPa or more, preferably 120 GPa or less, more preferably 100 GPa or less, and even more preferably 80 GPa or less. Within the above range, the above formula (2) is easily satisfied. Furthermore, the method for determining the storage modulus E2 of the laminate at 280°C is the method described in the examples.
[0056] That is, by simultaneously satisfying equations (1) and (2) above, the laminate of the present invention can reduce the amplitude of the inorganic substrate during operation of the laminate while suppressing the warping of the laminate during high-temperature heating. The values of equations (1) and (2) above can be controlled by selecting a transparent heat-resistant polymer film with suitable thickness and elastic modulus, or by adjusting the thickness of the inorganic substrate.
[0057] In this invention, it is preferable that the warpage of the laminate of the transparent heat-resistant polymer film and the inorganic substrate is less than 500 μm after heating at 280°C for 1 hour. When the warpage of the laminate is less than 500 μm after heating at 280°C for 1 hour, i.e. after the high-temperature process, it is easier to implement operations using lifting pins and robotic arms. Furthermore, it is less likely to cause obstacles when coating is required by a coating machine in subsequent processes.
[0058] <Adhesive> In this invention, there is substantially no adhesive layer between the inorganic substrate and the transparent heat-resistant polymer film. Here, the adhesive layer refers to a layer with a Si (silicon element) content of less than 10% (less than 10% by mass). Furthermore, the term "substantially not used" (meaning "not present") is used because the thickness of the adhesive layer between the inorganic substrate and the transparent heat-resistant polymer film is preferably 0.4 μm or less, more preferably 0.3 μm or less, even more preferably 0.2 μm or less, particularly preferably 0.1 μm or less, and most preferably 0 μm.
[0059] <Silane Coupling Agent (SCA)> In the laminate, a silane coupling agent layer is preferably present between the transparent heat-resistant polymer film and the inorganic substrate. In this invention, the silane coupling agent refers to a compound containing 10% by mass or more Si (silicon element). By using the silane coupling agent layer, the following effects can be achieved: the intermediate layer between the transparent heat-resistant polymer film and the inorganic substrate is thinner, less degassing occurs during heating, and it is difficult to dissolve even in wet processes; even if dissolution occurs, it is only in trace amounts. The silane coupling agent preferably contains a higher content of silicon oxide to improve heat resistance, and is particularly preferred to be a product with heat resistance at around 400°C. The thickness of the silane coupling agent layer is preferably less than 0.2 μm. For use in flexible electronic devices, a thickness of 100 nm or less (0.1 μm or less) is preferred, more preferably 50 nm or less, and even more preferably 10 nm or less. A thickness of approximately 0.10 μm or less can be obtained using conventional methods. Furthermore, in processes where a low silane coupling agent content is highly desirable, a thickness of 5 nm or less can also be used. Below 1nm, there is a concern that the peel strength may decrease or that some parts may not adhere properly, so 1nm or above is preferred.
[0060] The silane coupling agent used in this invention is not particularly limited, but silane coupling agents having amino or epoxy groups are preferred. Specific examples of silane coupling agents include N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylene)propylamine, and 2-(3,4-epoxycyclohexyl)ethyl... 3-Epoxypropoxypropyltrimethoxysilane, 3-Epoxypropoxypropylmethyldiethoxysilane, 3-Epoxypropoxypropyltriethoxysilane, Vinyltrichlorosilane, Vinyltrimethoxysilane, Vinyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-epoxypropoxypropyltrimethoxysilane, 3-epoxypropoxypropylmethyldiethoxysilane, 3-epoxy Propoxypropyltriethoxysilane, p-styryltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane hydrochloride, 3-ureapropyltriethoxysilane, 3-chloropropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, bis(triethoxysilylpropyl)tetrasulfide, 3-isocyanatepropyltriethoxysilane, tri-(3-trimethoxysilylpropyl)isocyanurate, chloromethylphenylethyltrimethoxysilane, chloromethyltrimethoxysilane, etc. Preferred examples include N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylene)propylamine, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-epoxypropoxypropyltrimethoxysilane, 3-epoxypropoxypropylmethyldiethoxysilane, 3-epoxypropoxypropyltriethoxysilane, aminophenyltrimethoxysilane, aminophenylethyltrimethoxysilane, and aminophenylaminomethylphenylethyltrimethoxysilane. When heat resistance is required in the process, substances in which Si and amino groups are linked by aromatic compounds are preferred.
[0061] The adhesive strength between the aforementioned transparent heat-resistant polymer film and the aforementioned inorganic substrate is preferably 0.3 N / cm or less. Therefore, after a device is formed on the transparent heat-resistant polymer film, peeling between the transparent heat-resistant polymer film and the inorganic substrate becomes very easy. Thus, mass-producible device connectors can be manufactured, and the manufacture of flexible electronic devices becomes easier. The aforementioned adhesive strength is preferably 0.25 N / cm or less, more preferably 0.2 N / cm or less, even more preferably 0.15 N / cm or less, and particularly preferably 0.1 N / cm or less. Furthermore, 0.01 N / cm or more is preferred. From the perspective of preventing the laminate from peeling when a device is formed on the transparent heat-resistant polymer film, 0.02 N / cm or more is more preferred, even more preferably 0.03 N / cm or more, and particularly preferably 0.05 N / cm or more is preferred. The aforementioned adhesive strength is the value of the laminate after heat treatment at 100°C for 10 minutes in an atmospheric atmosphere following bonding the transparent heat-resistant polymer film to the aforementioned inorganic substrate (initial adhesive strength). Furthermore, it is preferable that the laminate after further heat treatment in a nitrogen atmosphere at 200°C for 1 hour following the initial adhesive strength test also has an adhesive strength within the above range (adhesive strength after heat treatment at 200°C).
[0062] The laminate of the present invention can be manufactured, for example, by the following process: At least one side of an inorganic substrate is pretreated with a silane coupling agent; the silane-coupling agent-treated side is laminated with a transparent heat-resistant polymer film; and the laminate is obtained by laminating the two under pressure. Alternatively, at least one side of a transparent heat-resistant polymer film is pretreated with a silane coupling agent; the silane-coupling agent-treated side is laminated with an inorganic substrate; and the laminate is obtained by laminating the two under pressure. The pressure application methods include conventional pressing or lamination in the atmosphere or pressing or lamination in a vacuum. However, to obtain stable adhesive strength across the entire surface, atmospheric lamination is preferred for large-sized laminates (e.g., greater than 200 mm). Conversely, for small-sized laminates less than 200 mm, vacuum pressing is preferred. A vacuum level of approximately 10 Torr or less, obtained using a conventional oil-sealed rotary pump, is sufficient. A pressure of 1 MPa to 20 MPa is preferred, and more preferably 3 MPa to 10 MPa is preferred. High pressure may damage the substrate, while low pressure may result in gaps in the seal. The preferred temperature is 90°C to 300°C, more preferably 100°C to 250°C. High temperatures may damage the film, while low temperatures may result in weak adhesion.
[0063] The laminate of the present invention can be fabricated by coating an inorganic substrate with a transparent heat-resistant polymer precursor solution or a transparent heat-resistant polymer solution and then heating it.
[0064] Fabrication of Flexible Electronic Devices Using the aforementioned laminate and existing equipment and processes for manufacturing electronic devices, flexible electronic devices can be easily fabricated. Specifically, electronic components or wiring (electronic devices) are formed on a transparent heat-resistant polymer film of the laminate, and flexible electronic devices can be fabricated by peeling the entire heat-resistant polymer film off the laminate. The electronic devices referred to in this specification are active components such as circuit boards, transistors, and diodes with single-sided, double-sided, or multi-layer structures that bear electrical wiring, as well as electronic circuits containing passive components such as resistors, capacitors, and inductors. In addition, it also refers to sensor elements that sense pressure, temperature, light, humidity, etc., biosensor elements, light-emitting elements, image display elements such as liquid crystal displays, electrophoretic displays, and self-emissive displays, wireless or wired communication elements, computing elements, storage elements, MEMS elements, solar cells, thin-film transistors, etc.
[0065] In the manufacturing method of the flexible electronic device of the present invention, after forming the device on the transparent heat-resistant polymer film of the laminate prepared by the above method, the transparent heat-resistant polymer film is peeled off from the inorganic substrate.
Example
[0066] The embodiments of the present invention will be described in detail below, but the present invention is not limited to the following embodiments as long as it does not exceed the spirit of the present invention.
[0067] Preparation of heat-resistant polymer films The membranes F5 to F8 used in the comparative examples used commercially available colored substances. F5: XENOMAX (registered trademark) F38LR2 (polyimide film manufactured by Toyobo Co., Ltd., 38μm thick) F6: XENOMAX (registered trademark) F15LR2 (polyimide film manufactured by Toyobo Co., Ltd., 15μm thick) F7: UPILEX (registered trademark) 25S (polyimide film manufactured by Ube Industries, Ltd., 25μm thick) F8: XENOMAX (registered trademark) F50LR2 (polyimide film manufactured by Toyobo Co., Ltd., 50μm thick)
[0068] <Preparation of Polyamic Acid Solution A1> After purging the reaction vessel equipped with a nitrogen inlet pipe, reflux pipe, and stir bar with nitrogen, 33.36 parts by mass of 2,2'-bis(trifluoromethyl)diaminobiphenyl (TFMB), 270.37 parts by mass of N-methyl-2-pyrrolidone (NMP), and a dispersion ("Snowtex (registered trademark) DMAC-ST") formed by dispersing colloidal silica in dimethylacetamide were added. The amount of silica was such that it accounted for 0.14% of the total solid polymer components in the polyamic acid solution, and it was completely dissolved. Then, 9.81 parts by mass of 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA), 11.34 parts by mass of 3,3',4,4'-biphenyltetracarboxylic acid (BPDA), and 4.85 parts by mass of (ODPA) were added in batches in solid form, and the mixture was stirred at room temperature for 24 hours. Then, 165.7 parts by mass of DMAc were added for dilution to obtain a polyamic acid solution A1 with a solid content of 18% by mass and a specific viscosity of 2.7 dl / g (molar ratio of TFMB / / CBDA / BPDA / OPDA = 1.00 / / 0.48 / 0.37 / 0.15).
[0069] <Fabrication of Transparent Heat-Resistant Polymer Film F1> Using a coating machine, polyamic acid solution A1 was coated onto the unlubricated surface of polyethylene terephthalate film A4100 (manufactured by Toyobo Co., Ltd.), and the final film thickness was adjusted to 25 μm. It was then dried at 90–110°C for 10 minutes. After drying, the self-supporting polyamic acid film was peeled from the support and passed through a pin plate tenter frame equipped with pin plates. The film was fixed by inserting pins into the ends, and the pin plate spacing was adjusted to prevent film breakage and unnecessary slack. The film was heated at 250°C for 3 minutes, 300°C for 3 minutes, and 370°C for 6 minutes to induce the imidization reaction. After cooling to room temperature for 2 minutes, the poorly planar portions at both ends of the film were cut off using a cutting machine, and the film was wound into a roll to obtain a 500 m long, 450 mm wide polyimide film F1.
[0070] <Production of Transparent Heat-Resistant Polymer Film F2> Except for achieving a final film thickness of 15 μm, transparent heat-resistant polymer film F2 was obtained using the same method as transparent heat-resistant polymer film F1.
[0071] <Preparation of Polyimide Solution A2> Nitrogen gas was introduced into a reaction vessel equipped with a nitrogen inlet tube, a Dean-Stark apparatus, a reflux tube, a thermometer, and a stir bar. Simultaneously, 19.86 parts by mass of 4,4'-diaminodiphenyl sulfone (4,4'-DDS), 4.97 parts by mass of 3,3'-diaminodiphenyl sulfone (3,3'-DDS), and 80 parts by mass of γ-butyrolactone (GBL) were added. Then, at room temperature, 31.02 parts by mass of 4,4'-oxydiphthalic dianhydride (ODPA), 24 parts by mass of GBL, and 13 parts by mass of toluene were added. The internal temperature was then raised to 160°C and refluxed at 160°C for 1 hour to induce imidization. After imidization, the temperature was raised to 180°C, and the reaction continued while toluene was separated. After reacting for 12 hours, the oil bath was removed and the temperature was restored to room temperature. GBL was then added to achieve a solid content of 20% by mass, resulting in a polyimide solution A2 with a specific viscosity of 0.70 dl / g (molar ratio of 4,4'-DDS / 3,3'-DDS / / ODPA = 0.80 / 0.20 / 1.00).
[0072] <Production of Transparent Heat-Resistant Polymer Film F3> Using a coating machine, polyimide solution A2 is coated onto the unlubricated surface of polyethylene terephthalate film A4100 (manufactured by Toyobo Co., Ltd.), and the final film thickness is adjusted to 25 μm. The polyethylene terephthalate film A4100 is then passed through a hot air furnace and wound up, and dried at 100°C for 10 minutes. After drying, the self-supporting polyamic acid film is peeled from the support and passed through a needle plate tenter frame equipped with needle plates. The film is secured by inserting needles into the ends, and the needle plate spacing is adjusted to prevent film breakage and unnecessary slack. The imidization reaction is carried out by heating at 200°C for 3 minutes, 250°C for 3 minutes, and 300°C for 6 minutes. Then, after cooling to room temperature for 2 minutes, the poorly planar parts at both ends of the film are cut off with a cutting machine and wound into a roll to obtain a 500m long, 450mm wide polyimide film F3.
[0073] <Production of Transparent Heat-Resistant Polymer Film F4> Except for changing the final film thickness to 15 μm, transparent heat-resistant polymer film F4 was obtained using the same method as transparent heat-resistant polymer film F3.
[0074] <Inorganic substrate> Commercially available products were used for the inorganic substrates S1 to S3. S1: OA-10G (manufactured by Nippon Electric Glass Co., Ltd., thickness 0.5mm) S2: OA-10G (manufactured by Nippon Electric Glass Co., Ltd., thickness 0.3mm) S3: OA-10G (manufactured by Nippon Electric Glass Co., Ltd., thickness 0.7mm)
[0075] <Determination of the thickness of heat-resistant polymer films> The thickness of the heat-resistant polymer film was measured using a micrometer (Feinpruf, Millitron 1245D). The results are shown in Table 1.
[0076] <Determination of the thickness (T1) of the laminate> The thickness (T1) of the laminate was measured using a high-precision digital micrometer (Mitutoyo MDH-25M, manufactured by Mitutoyo Corporation). The results are shown in Table 1.
[0077] <Tension Modulus of Heat-Resistant Polymer Films> Heat-resistant polymer films F1 to F8 were cut into 100mm × 10mm strips in both the mechanical direction (MD direction) and the width direction (TD direction) to serve as test pieces. The tensile modulus in both the MD and TD directions was measured using a tensile testing machine (Shimadzu Autograph AG-5000A) at a tensile speed of 50mm / min and a chuck spacing of 40mm. The results are shown in Table 1.
[0078] <Tensive modulus of laminate (E1)> The laminate of the inorganic substrate and the heat-resistant polymer film was cut into 100mm × 10mm strips in both the shear direction (MD direction) and the width direction (TD direction) using a glass cutter to serve as test pieces. The tensile modulus (E1) in both the MD and TD directions was measured using a tensile testing machine (Shimadzu Autograph AG-5000A) at a tensile speed of 50mm / min and a chuck spacing of 40mm. The results are shown in Table 1.
[0079] <Storage modulus (E2) of the laminate at 280°C> The storage modulus of the laminate was calculated using the following formula after separately measuring the storage modulus of the transparent heat-resistant polymer film and the inorganic substrate. First, the storage modulus of the heat-resistant polymer film was measured using a Q800 instrument manufactured by TA Instruments Co., Ltd. The initial load was 0.02 N, the frequency was 10 Hz, the sample width was 5 mm, the chuck spacing was 20 mm, and the measurement was performed at a speed of 5 °C / min within the range of 30 °C to 400 °C. The storage modulus at 280 °C was measured. If the measurement could not be performed beyond the upper limit of the instrument, the dynamic viscoelasticity of the heat-resistant polymer film was measured under the same conditions. The storage modulus of the inorganic substrate was measured using an itkDVA-225 instrument, and the storage modulus (E2) of the laminate at 280 °C was calculated using the following formula. The storage modulus (E2) of the laminate at 280℃ = {Storage modulus of the heat-resistant polymer film at 280℃ × Thickness of the heat-resistant polymer film / (Thickness of the laminate)} + {Storage modulus of the inorganic substrate at 280℃ × Thickness of the inorganic substrate / (Thickness of the laminate)}
[0080] <Heat shrinkage rate of heat-resistant polymer film> A 15×20cm rectangular sample was cut from the heat-resistant polymer film at positions 10cm from the L end, the center, and 10cm from the R end. This rectangle was conditioned at 23°C and 50% RH for 24 hours, and then marked at 10cm intervals. It was then heated at 250°C for 1 hour, and again conditioned at 23°C and 50% RH for 24 hours. The heat shrinkage rate was measured by measuring the marked intervals. Length measurements were performed using a VISION MEASUREING MACHINE manufactured by Mitutoyo Co., Ltd., with n=2 measurements performed for each type of film. The results are shown in Table 1.
[0081] <Coefficient of linear expansion (CTE) of heat-resistant polymer films> For heat-resistant polymer films (polyimide films) F1 to F8, the stretch rate was measured in both the mechanical direction (MD direction) and the width direction (TD direction) under the following conditions: the stretch rate / temperature was measured at 15°C intervals, such as 30°C to 45°C and 45°C to 60°C, up to 300°C. The average value of all measured values was calculated as the CTE. The results are shown in Table 1. Machine name: TMA4000S manufactured by MAC Science Sample length: 20mm Sample width: 2mm Temperature to start heating: 25℃ End of heating temperature: 300℃ Heating rate: 5℃ / min Atmosphere: Argon
[0082] <Total light transmittance> The total light transmittance (TT) of the heat-resistant polymer film was measured using a HAZEMETER (NDH5000, manufactured by Nippon Denshoku Co., Ltd.). A D65 lamp was used as the light source. Furthermore, the same measurement was performed three times, and the arithmetic mean was taken. The results are shown in Table 1.
[0083] <Yellow Index (YI)> Using a colorimeter (ZE6000, manufactured by Nippon Denshoku Co., Ltd.) and a C2 light source, the tristimulus values (XYZ) of the heat-resistant polymer film were measured according to ASTM D1925, and the yellowness index (YI) was calculated using the following formula. Furthermore, the same measurement was performed three times, and the arithmetic mean was taken. The results are shown in Table 1. YI = 100 × (1.28X - 1.06Z) / Y
[0084] <Haze> The haze of the heat-resistant polymer film was measured using a HAZEMETER (NDH5000, manufactured by Nippon Denshoku Co., Ltd.). A D65 lamp was used as the light source. Furthermore, the same measurement was performed three times, and the arithmetic mean was taken. The results are shown in Table 1.
[0085] (Example 1) The method for coating the inorganic substrate S1 with silane coupling agent was performed using the apparatus shown in Figure 1. Figure 1 is a schematic diagram of the apparatus for coating the inorganic substrate S1 with silane coupling agent. The inorganic substrate S1 was used (cut into 370mm × 470mm dimensions). Furthermore, the inorganic substrate S1 was a substrate that had been dry-cleaned by irradiation with a UV / O3 irradiator (LAN Technical SKR1102N-03) for 1 minute after being washed with pure water and dried. 150g of 3-aminopropyltrimethoxysilane (silane coupling agent, Shin-Etsu Chemical KBM903) was added to a 1L reagent container, and the outer water bath was heated to 43°C. Then, the steam and clean, dry air were introduced into the processing chamber. The gas flow rate was set to 25L / min, and the substrate temperature was 24°C. The temperature of the clean, dry air was 23°C, and the humidity was 1.2% RH. Since the exhaust was connected to a negative pressure exhaust port, a differential pressure gauge was used to confirm that the processing chamber had a negative pressure of approximately 10Pa.
[0086] Next, a heat-resistant polymer film F1 (360mm × 460mm) was laminated onto the aforementioned silane coupling agent layer to obtain a laminate. A laminator manufactured by MCK Corporation was used for lamination, with the following conditions: compressed air pressure 0.6MPa, temperature 22°C, humidity 55%RH, and lamination speed 50mm / sec. This F1 / S1 laminate was then heated at 110°C for 10 minutes to obtain an inorganic substrate / heat-resistant polymer film laminate.
[0087] (Examples 2-4, Comparative Examples 1-4) Except for changing the combination of the inorganic substrate and the heat-resistant polymer film, the same operation as in Example 1 was performed. The combinations are shown in Table 1. In addition, since the polymer films in Comparative Examples 1 to 4 are colored films, the total light transmittance, YI, haze, and CTE were not measured.
[0088] <Determination of 90° Adhesive Strength (Peel Strength)> For the laminate obtained as described above, the 90° peel strength between the inorganic substrate and the heat-resistant polymer film was measured. The conditions for determining the initial peel strength at 90° are as follows. The film is peeled off at a 90° angle relative to the inorganic substrate. The measurement was performed 5 times, and the average value was taken as the measured value. Measuring apparatus: Autograph AG-IS, manufactured by Shimadzu Corporation Measurement temperature: room temperature (25℃) Peeling speed: 100mm / min Atmosphere: Grand The width of the sample was measured to be 2.5 cm.
[0089] <Warping of Layered Structures> The laminate obtained as described above was heated at 280°C for 1 hour. After heating, the laminate was allowed to return to room temperature and then placed in a nitrogen-purged chamber for 24 hours. The laminate was then removed from the chamber, and within 10 minutes, the inorganic substrate was placed face down on a platform. A 500 μm thick spacer sheet was inserted into each of the four corners of the laminate. The results were evaluated according to the following criteria. The results are shown in Table 1. The case where the grouting piece can be inserted into the corner without any obstruction is marked as ×. In the case where the gap filler in the inorganic substrate is stuck at one or fewer corners, and the inorganic substrate is in contact with the gap filler but can only insert at one corner, this is called △. In inorganic substrates, the case where two or three corners are blocked by the gap filler is 0. The case where the gap filler is stuck in any corner of the inorganic substrate is ◎.
[0090] Vibration of laminated bodies The fabricated laminate was placed on the worktable with the membrane side down. A camera (Keyence VH-Z20R) was positioned 15cm above the worktable. A suction lift (Bohole 50kg) was set up with suction cups arranged along the center and long side of the laminate. Holding the handle of the suction lift, the laminate was raised 15cm upwards at a speed of 10cm / second. The amplitude of the laminate was measured based on the captured video. The results are shown in Table 1.
[0091] Table 1
Claims
1. A laminated body, characterized in that, It is a laminate of a heat-resistant polymer film and an inorganic substrate, wherein there is no adhesive layer with a thickness of more than 0.4 μm between the inorganic substrate and the heat-resistant polymer film. The heat-resistant polymer film is a flexible transparent heat-resistant polyimide film with a total light transmittance of more than 75%. The tensile modulus E1 and the thickness T1 of the laminate satisfy equation (1), where the unit of tensile modulus E1 is GPa and the unit of thickness T1 is μm. 25000 ≤ E1×T1 (1) Furthermore, the energy storage modulus E2 of the laminate at 280℃ and its thickness T1 satisfy equation (2), where the unit of energy storage modulus E2 is GPa and the unit of thickness T1 is μm: E2×T1 ≤ 52000 (2) The heat-resistant polymer film has a thermal shrinkage rate of -0.9% to +0.9% when heated from 23°C to 250°C. The heat-resistant polymer film has a storage modulus of 0.5 GPa or higher and 9 GPa or lower at 280°C. The warpage of the laminate after heating at 280°C for 1 hour is less than 500 μm.
2. The laminated body according to claim 1, characterized in that, The tensile modulus of the heat-resistant polymer film is above 3.5 GPa and below 9 GPa.
3. The laminate according to claim 1 or 2, characterized in that, The outer diameter of the inorganic substrate is 400 mm or more.
4. The laminate according to claim 1 or 2, wherein, The thickness of the heat-resistant polymer film is greater than 3 μm and less than 50 μm.
5. The laminate according to claim 1 or 2, wherein, A silane coupling agent layer with a thickness of less than 100 nm is present between the inorganic substrate and the heat-resistant polymer film.
Citation Information
Patent Citations
Tankasuisononetsubunkaiho
JP1976052104A
Method of toning wood
JP1981099606A
Laminated body, manufacturing method thereof, and laminated circuit board
CN102256785A